2020
DOI: 10.1115/1.4047140
|View full text |Cite
|
Sign up to set email alerts
|

The Master Sinter Curve and Its Application to Binder Jetting Additive Manufacturing

Abstract: The master sinter curve (MSC) is an empirical model used to predict the density of a part after being sintered. The model is typically applied to components that undergo isotropic shrinkage. Parts manufactured using binder jetting additive manufacturing (BJAM) are known to have nonuniform powder systems and high levels of anisotropy. This work explores the application of the master sinter curve to components made by BJAM. Cylindrical samples were manufactured with the long axis parallel (vertical), perpendicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This tendency will be analysed more in detail by using the anisotropic factors in the next section. Previous studies [5,10,11,19,20] have shown that BJ components usually present larger final shrinkages along the building direction. However, no evidence on how this anisotropy is developed during the sintering process was presented before.…”
Section: Resultsmentioning
confidence: 99%
“…This tendency will be analysed more in detail by using the anisotropic factors in the next section. Previous studies [5,10,11,19,20] have shown that BJ components usually present larger final shrinkages along the building direction. However, no evidence on how this anisotropy is developed during the sintering process was presented before.…”
Section: Resultsmentioning
confidence: 99%
“…The linear shrinkage values calculated in the three directions confirm that the powder packing in the 100LT samples is lower, thus the number of voids to be filled during the sintering treatment and the J o u r n a l P r e -p r o o f resulting shrinkage is larger. In addition, it can be noticed that the shrinkage along the building direction is higher because of improper powder packing between layers [27,48,72,73].…”
Section: Microstructural Analysis Of the Sintered Samplesmentioning
confidence: 99%
“…Once the heating steps were completed, the samples were cooled down to room temperature with a 10°C min −1 cooling rate. This fast cooling prevented any significant amount of sintering from occurring during the ramp-down phase, allowing the shrinkage measurements on cooling to be used for calculating the coefficient of thermal expansion (CTE) (Wheat et al , 2020). The CTE value is required to correct the dilatometry data to represent only shrinkage due to sintering, eliminating the contribution of the thermal expansion/shrinkage of the copper particles, which individually behave as a pore-free volume when they are subjected to a thermal cycle.…”
Section: Methodsmentioning
confidence: 99%